INSTRUMEN ADMINISTRATIF PEMBATASAN PENGGUNAAN FASILITAS NEGARA OLEH CALON PRESIDEN PETAHANA DIKAITKAN DENGAN UPAYA PEMILIHAN UMUM YANG DEMOKRATIS (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
State facilities are finance means and infrastructure from APBN and or APBD. The use ofstate facilities is essentially recommended in the interests of the government. In accordance withcurrent regulations of the law regarding the use of state facilities, facilities of state are indeed usedfor accommodation and continuity in government practices. But it’s different in elections, publicfacilities are not allowed to be used for the campaign’s benefit. That way any facilities attached tothe office of a state officials, including incumbent presidential candidates are absolutely notallowed to be used to campaign.So while state facilities could still be used by incumbentpresidential candidates, then it would not in thid case reflect a democratic election that conformsto the principle of elections. However, on the other hand the position of president is still attachedto the incumbent presidential candidate. Where based on the constitution, the president is both ahead of state an a head of government that has duties and functions.A president has the right to usethe state facility attached to himself to perform his duties and functions as president. So the safetyof a president must be maintained. In this context, no one of current presidential securityprocedures can be left behid.The study uses normative-law research typology also called doctrinal law research, whichdeals more specifically with law synchronization, as it relates to the use of state facilities byincumbent presidential candidates that would later be.The result of the study by the author is that administrative instruments of limitation of theuse of state facilities by incumbent presidential candidates have not been able to afford restrictionson incumbent presidential candidates in accordance with the basic principles of elections. Whileregulatory restrictions on the use of state facilities for government official other than the incumbentpresidential candidates to elections are clearly established, both for incumbent participants andother participants, the rule of limitation of state facilities for reelaction presidents is not the sameas other government officials who reelaction. Based on the decision of the constitutional courtnumber 10/PUU-XVII/2019 explaining that the incumbent presidential candidates as president whohas a position that cannot be separated from him is not to take a leave. Nevertheless, theconstitutional court ruled that a ban be placed on the incumbent presidential candidates for thecampaign so as not to abuse his position asa successor because there was something inherent inthe president according to article 305 of constitution number 17 in 2017, where this will not berelinquished from the future incumbent presidential candidates.Keywords: State Facility-Incumbent Presidential Candidates-Administrative Instruments